2007
DOI: 10.1097/rlu.0b013e318053ed4d
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Incidental Detection of Unsuspected Skeletal Tuberculosis by Bone Scintigraphy Should Not Be Overlooked

Abstract: Our results indicate that pulmonary or systemic tuberculosis is not a prerequisite for skeletal tuberculosis. Skeletal tuberculosis should be among the differential diagnoses when there is a positive bone scan in patients without a malignancy in an endemic region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…7,8 However, in our case, no tuberculosis of the lungs or any other organs except for the spine was identified, which was consistent with the notion that in many Asian countries skeletal tuberculosis did not always have concurrent extraskeletal tuberculosis. 9 Secondly, it has been well published that 2 coexisting different types of malignancies can both have significant FDG uptake on PET scans and will frequently be interpreted as a single type of malignancy with metastases. 10 -13 In comparison, we reported that 2 coexisting distinct nonmalignant processes masqueraded as primary malignancy with metastases on PET or PET/CT.…”
Section: Clinical Nuclear Medicine • Volume 34 Number 4 April 2009mentioning
confidence: 99%
“…7,8 However, in our case, no tuberculosis of the lungs or any other organs except for the spine was identified, which was consistent with the notion that in many Asian countries skeletal tuberculosis did not always have concurrent extraskeletal tuberculosis. 9 Secondly, it has been well published that 2 coexisting different types of malignancies can both have significant FDG uptake on PET scans and will frequently be interpreted as a single type of malignancy with metastases. 10 -13 In comparison, we reported that 2 coexisting distinct nonmalignant processes masqueraded as primary malignancy with metastases on PET or PET/CT.…”
Section: Clinical Nuclear Medicine • Volume 34 Number 4 April 2009mentioning
confidence: 99%
“…MRI can be used to discriminate between abscesses and granulation tissue, delineate soft-tissue mass and identify the amount of bone destruction (16); however, MRI may not be appropriate for whole-body imaging as it is expensive and time-consuming (17). Bone scans, on the other hand, play an important role in the diagnosis and evaluation of TB (17,18), since they can detect unsuspected osseous TB in patients without known systemic diseases, particularly patients suffering from pain but without known malignancies. Bone scans also help to determine the optimal biopsy site and the most suitable area for insightful MRI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Bone scans also help to determine the optimal biopsy site and the most suitable area for insightful MRI imaging. Bone TB should be considered among the differential diagnoses when positive bone scans are observed in patients with unknown causes of bone pain, particularly in patients who do not have a known history of malignancy (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Most positive findings on bone scan in relatively young patients with back pain are due to non-malignant etiology, such spondylolysis, osteomyelitis, or osteoid osteoma. [9][10][11][12][13][14][15] However, different malignant disorders, 16,17 including the current one, can also be incidentally identified in young patients with back pain.…”
Section: Figurementioning
confidence: 94%